Gender Roles and Identity in Visual Representations of Primary Education Textbooks in West Bengal and Bangladesh - Nandi, Ankur; Hader, Tarini; Das, Tapash (EDUCARE: Journal of Primary Education, 2025)
Textbooks serve as a vehicle for social change. From childhood in school through textbooks and classroom experiences students embrace gender socialization, societal norms, and beliefs, gender roles, inequality, and bias. So, it is very important to make textbooks gender-neutral, to do this, textbook analysis is required. This study investigates the images used in textbooks of primary education in West Bengal and national curriculum and textbook Board, Govt. of Bangladesh, to examine gender stereotypes and bias. The study adopted qualitative and documentary research approaches through content analysis. The findings demonstrate that gender patriarchy and bias are reflected through visual imagery in textbooks. Images often lack representation of women and tend to portray them engaging in indoor tasks such as domestic and household work, or menial labor. Meanwhile, men are predominantly shown in outdoor, professional, and leadership roles, reinforcing gender disparities in identity and societal roles. There is a limited attempt to showcase gender neutrality in primary-level language textbooks in West Bengal and Bangladesh, and there's minimal encouragement for gender reflection, hindering the development of sustainable perceptions of gender roles in society. The findings of the study provide a foundation for policy changes at the state or national level to ensure the development and implementation of guidelines that promote gender-neutral content in educational materials and are useful for textbook development agencies, textbook writers, and teachers in developing a gender-sensitive curriculum, and textbooks.